Stabilization of visual acuity with photodynamic therapy in eyes with chorioretinal anastomoses - Silva, Rufino M. (2004)
Purpose(1) To evaluate, in a non-randomized, institutional, prospective study, the efficacy of photodynamic therapy with Visudyne (PDT) in neovascular age-related macular degeneration (AMD) eyes with chorioretinal anastomoses (CRA). (2) To review, in a retrospective study and for comparison, the natural evolution of neovascular AMD eyes with CRA.MethodsProspective clinical and angiographic study of 17 consecutive eyes with CRA, treated with PDT. Retrospective clinical and angiographic study of the natural course of 17 consecutive patients with CRA. Masked best-corrected visual acuity (VA) and angiographic features at baseline and during the period of one year were evaluated.ResultsThe two groups presented similar characteristics at baseline regarding age, sex, initial VA, duration of follow-up and angiographic features. PDT-treated eyes showed, at 1-year follow-up, VA stabilization or improvement in 73.3% of the eyes, no cases with very severe VA loss, and no fluorescein leakage in 46.6% of the eyes. In contrast, at 1-year follow-up the natural evolution of CRA was characterized by severe or very severe VA loss in 69% of the eyes and statistically significant mean VA loss ( P=0.001) with persistence of fluorescein leakage in all cases.ConclusionThe natural history of AMD eyes with CRA leads to progressive and dramatic VA loss, which is associated with blindness in most of the cases. PDT with verteporfin can offer some benefit to these patients, allowing VA stabilization or improvement in more than two thirds of the cases, at one year.